Fabrication of broadband antireflection coatings using broadband optical monitoring mixed with time monitoring - 吕起鹏 邓淞文 张绍骞 公发全 李刚 (Chinese physics B, 2017)
Multi-layer optical coatings with complex spectrum requirements, such as multi-band pass filters, notch filters, and ultra-broadband antireflection coating, which usually contain very thin layers and sensitive layers, are difficult to be fabricated using a quartz crystal monitoring method or a single wavelength optical monitoring system（SWLOMS）. In this paper, a broadband antireflection（AR） coating applied in the wavelength range from 800 nm to 1800 nm was designed and deposited by ion beam sputtering（IBS）. Ta2O5 and Si O2 were chosen as high and low refractive index coating materials,respectively. The optimized coating structure contains 9 non-quarter-wave（QW） layers totally with ultra-thin layers and sensitive layers in this coating stack. In order to obtain high transmittance, it is very important to realize the thickness accurate control on these thin layers and sensitive layers. A broadband optical monitoring mixed with time monitoring strategy was successfully used to control the layer thickness during the deposition process. At last, the measured transmittance of AR coating is quite close to the theoretical value. A 0.6% variation in short wavelength edge across the central 180 mm diameter is demonstrated. A spectrum shift of less than 0.5% for 2 continuous runs is also presented.